2015
DOI: 10.1371/journal.pone.0134153
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Consumption and Related Behaviors in Brazil: Evidence from the 2013 National Health Survey (PNS 2013)

Abstract: This study uses data from a nationally representative household survey (the 2013 National Health Survey, n = 62,986) to describe patterns of alcohol consumption and related behaviors among Brazilian adults. Analyses include descriptive and multivariable Poisson regression for self-reports in the past 30 days of: drinking any alcohol, binge drinking, binge drinking 4 or more times, and driving after drinking (DD); as well as age of alcohol consumption initiation. Results show that current drinking prevalence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 40 publications
1
48
0
7
Order By: Relevance
“…Previous studies also found that men drink more than women 17,18 , and differences in consumption refer to the amount and way they drink, besides social and health consequences to which they are subject to 2 . Due to biological factors, the intake of the same amount of alcohol produces higher alcoholic concentration in the blood of women 19 , which could explain the trend of men drinking in higher amounts and more frequently than women.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies also found that men drink more than women 17,18 , and differences in consumption refer to the amount and way they drink, besides social and health consequences to which they are subject to 2 . Due to biological factors, the intake of the same amount of alcohol produces higher alcoholic concentration in the blood of women 19 , which could explain the trend of men drinking in higher amounts and more frequently than women.…”
Section: Discussionmentioning
confidence: 93%
“…A study using data from the NHS to evaluate alcohol consumption showed that residents in the Northeast and Central-West regions of Brazil have the highest levels of binge drinking and driving under the influence [49]. Another study that analyzed NHS data to determine alcohol consumption showed a higher prevalence of binge drinking in the North, Northeast, and Central-West regions compared with the South and Southeast regions of Brazil [50].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al, [18] reported a higher prevalence use of alcohol among young male, aged between 15-24 years of age compared to females in Asian Countries. Macinko et al, [19] reported a higher alcohol use among males aged 25-35 years compared to females in a health survey study in Brazil. In addition, Evans et al [20] confirmed that males have a higher alcohol use among youth in the USA.…”
Section: Prevalence Of Alcoholic Beverage Usementioning
confidence: 95%